Expertsʼ Opinion on the Prenatal Therapy of Congenital Adrenal Hyperplasia (CAH) Due to 21-Hydroxylase Deficiency – Guideline of DGKED in cooperation with DGGG (S1-Level, AWMF Registry No. 174/013, July 2015) - Dörr, H. G.; Binder, G.; Reisch, N.; Gembruch, U.; Oppelt, P. G.; Wieacker, P.; Kratzsch, J. (Geburtshilfe und Frauenheilkunde, 2015)
Purpose: This guideline of the German Society of Pediatric Endocrinology and Diabetology (DGKED) is designed to be expertsʼ opinion on the current concept of prenatal therapy for congenital adrenal hyperplasia due to 21-hydroxylase deficiency (CAH). Several scientific medical societies have also participated in the guideline. It aims to offer guidance to physicians when they counsel affected families about prenatal therapy. Methods: The experts commissioned by the medical societies developed a consensus in an informal process. The consensus was subsequently confirmed by the steering committees of the respective medical societies. Recommendations: Prenatal CAH therapy is an experimental therapy. We recommend designing and using standardized protocols for the prenatal diagnosis, therapy and long-term follow-up of women and children treated prenatally with dexamethasone. If long-term follow-up is not possible, then prenatal therapy should not be performed.
Keywords: CAH; prenatal therapy; dexamethasone; off-label use